The effect of polymorphisms (174G> C and 572C> G) on the Interleukin-6 gene in coronary artery disease: a systematic review and meta-analysis - Salari, Nader; Mansouri, Kamran; Hosseinian-Far, Amin; Ghasemi, Hooman; Mohammadi, Masoud; Jalali, Rostam; Vaisi-Raygani, Aliakbar (Genes and environment, 2021)
Background Coronary Artery Disease (CAD) is caused by the blockage of the coronary arteries. it is argued that there has an association between the Interleukin-6 gene and the occurrence of atherosclerosis, coronary artery disease, Due to the short half-life and high variability of Interleukin-6 (IL-6), limited studies have been performed on the association of serum levels of interleukin-6 with coronary artery disease. The aim of this study is to investigate the relationship between IL-6 gene polymorphisms and coronary artery disease. Methods This study was conducted as a meta-analysis of selected articles with no lower time limit and upto March 2020. Articles related to the subject were obtained by searching several data sources,such as the SID, IranDoc, Scopus, Embase, Web of Science (ISI), PubMed, Science Direct, and Google Scholar databases. The heterogeneity of the studies was assessed using the I 2 index in the Comprehensive Meta-Analysis software. Results The GG genotype of the IL-6174 G> C polymorphism with a 0.8 odds ratio tended to reduce the risk of CAD by 20%. The odds ratio of CAD in CG and GG genotypes were found to be 1.16 and 1.48 times respectively, indicating the increasing effect of these two genotypes. In the IL-6-572 C>G polymorphism, CG and GG genotypes increased the risk of CAD by 1.21 and 1.27 times respectively, and the CC genotype tended to reduce the risk of CAD by 15%, considering the odds ratio of 0.85. Conclusion This study showed a relationship between IL-6174G> C and Interleukin-6 (IL-6) 572 C>G genes and coronary artery disease. Moreover, the protective effects of GG genotype in IL-6 gene 174 G> C and CC genotype in IL-6 gene 572 C>G gene were reported. The study also confirmed that the CG and CC genotypes of the G>C IL-6174 gene have an increasing effect on coronary artery disease. Moreover, CG and GG genotypes in the IL-6 gene 572 C>G increased the risk of developing CAD. It should be noted that the increased risk of developing CAD was limited to meta-analytic studies in reported literatures.